Religious Engineering: Analisis Perda Nomor 4 Tahun 2021 tentang Pedoman Penyelenggaraan Gerakan Etam Mengaji (GEMA) di Kabupaten Kutai Kartanegara - Haya, Dita Allika Fadia; Yulianingrum, Aulia Vivi (AL-SULTHANIYAH, 2025)
This study aims to examine Regional Regulation Number 4 of 2021 concerning Gerakan Etam Mengaji (GEMA) in Kutai Kartanegara Regency as a legal instrument rooted in local wisdom and Islamic values. Using a normative legal approach and Miles and Huberman’s interactive data analysis model, the research explores the regulation's content, its underlying philosophical values, and its role as a form of conservative religious engineering. The findings indicate that GEMA not only seeks to preserve the community's religious culture but also serves as a legal strategy to strengthen character development and Qur’anic literacy among students. This regulation represents a participatory legal framework supported by a reward system aimed at educational and religious institutions. GEMA exemplifies how local law can function both as a protector and driver of religious cultural values in the face of modernization.